Encryption facility for z/OS V1.2 OpenPGP support - Bari, Paola; Kappeler, Patrick; Granados, Saheem; Jon, Stanley; Rogers, Benjamin; Rogers, Ken; Schultz, Richard (IBM redbooks., 2007)
This book is about the OpenPGP support available in the Encryption Facility for z/OS V1.2 (Program Product 5655-P97). It begins with a discussion of the principles of operation of the OpenPGP protocol and a review of some basic cryptographic topics. It presents detailed steps for installing and configuring Encryption Facility for z/OS and implementing OpenPGP support.